GENERAL CONSIDERATION TO LIFT THE STUDENTS’ MOTIVATION LEVEL IN COUNTRIES WHERE ENGLISH IS A COMPULSORY SUBJECT - Christian Albert Lewier (JURNAL TAHURI, 2017)
In countries where English is taught as a compulsory subject, many students have suffered from not sufficiently achieving the objectives of English learning because the curriculum that treated them in ‘one size fits all’ paradigm. At the other side, teachers seem to lack the creativity in crafting their teaching approach and methodology that add to the problem that already exist. In Indonesia, curriculum is centralized where the consideration for the archipelagic teaching is neglected. As Dornyei (2001a) points out that school curriculum in most cases failed to adjust with the English learners’ preference to learn in fun and meaningful way. Probably, teachers are now left with the question how to lift the motivation of the students aside from the fact that curriculum plays particular role in their teaching and learning success.